Mutual Caring—Resolving Habituation through Awareness: Supporting Meaningful Learning from Projects. Issue 2 (April 2014) - Jugdev, Kam; Wishart, Paul
This study used Grounded Theory methodology and developed an emergent theory of Mutual Caring . The main concern was Habituation to ineffective lessons learned sharing practices. Habituation is resolved through Mutual Caring, a socially and psychologically adaptive process. Mutual Caring involves comfortable conversations, engaging/sharing, and developing self-confidence, resulting in an enhanced wisdom pool. This paper extends the emphasis on tangible knowledge-sharing mechanisms. Mutual Caring could lead to better outcomes, such as more accessible and usable knowledge, a project management wisdom pool, and criteria for improved dyadic relationships to enhance project learning.